2003
DOI: 10.1210/jc.2003-030407
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent Adrenaline Attenuates the Responsiveness to But Not the Release of Counterregulatory Hormones during Subsequent Hypoglycemia

Abstract: Hypoglycemia unawareness is thought to be the consequence of recurrent hypoglycemia, yet the underlying mechanism is still incompletely understood. The aim of the present study was to determine the role of antecedent elevated adrenaline in the pathogenesis of hypoglycemia unawareness. Sixteen healthy volunteers (eight of either sex) participated in two experiments, performed in random order and at least 3 wk apart. During the morning, three consecutive doses of 0.04, 0.06, and 0.08 microg.kg(-1).min(-1) of adr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…There is also evidence that recent antecedent epinephrine elevations do not cause HAAF (78). Epinephrine infusions did not reduce the plasma epinephrine (or glucagon) and neurogenic symtom responses to subsequent hypoglycemia in nondiabetic subjects.…”
Section: The Mechanism Of the Shift Of The Glycemic Thresholds For Symentioning
confidence: 92%
“…There is also evidence that recent antecedent epinephrine elevations do not cause HAAF (78). Epinephrine infusions did not reduce the plasma epinephrine (or glucagon) and neurogenic symtom responses to subsequent hypoglycemia in nondiabetic subjects.…”
Section: The Mechanism Of the Shift Of The Glycemic Thresholds For Symentioning
confidence: 92%
“…Ultimate plasma adrenaline concentrations were similar in men and women (7.96 6 0.47 versus 8.31 6 0.58 nmol/L, P = NS), and compatible with those attained under hypoglycemic conditions. 8 Adrenaline infusion caused a dose-dependent increase in heart rate in both men and women, but the increase was significant larger in men (20.3 6 1.4 versus 11.2 6 2.8 bpm, P , 0.01, Fig. 1).…”
Section: Resultsmentioning
confidence: 79%
“…These subjects also participated in a previous study. 8 All subjects were healthy and did not use any medication, except for oral contraceptives that were used by all female participants. The study was performed as a placebo controlled single blind crossover design and was approved by the medical ethics committee of the Radboud University Nijmegen Medical Center.…”
Section: Subjectsmentioning
confidence: 99%
“…Taken together, these data support the notion that repeated adrenergic activation during antecedent bouts of hypoglycaemia plays a fundamental role in suppressing the sympathoadrenal response to subsequent episodes of hypoglycaemia and that β‐adrenergic receptor blockers may be a useful therapeutic strategy to prevent the development of HAAF and improve hypoglycaemia awareness in patients with T1D. In contrast to these findings, de Galan and colleagues reported that prior administration of epinephrine to healthy human subjects did not affect autonomic or neuroglycopenic symptoms, nor did it impair the counterregulatory hormone responses 39 . Differences in the responses to epinephrine infusion between the two studies may be attributed to the amplitude and/or duration of epinephrine exposure, as well as the length of time between the epinephrine infusion and the clamp procedure.…”
Section: Discussionmentioning
confidence: 97%